ANALISIS KESULITAN BELAJAR SISWA PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM - Sri Santika Rahmawati; Reval Fathurrahman Yakub; Siti Aisyah Gunawan; Salwa Salsabila Putri Sulaiman; Afiyatun Kholifah (Jurnal Ilmu Pendidikan Islam, 2026)
This study aims to analyze the problems in the teaching of Islamic Cultural History (IS), the factors that cause students' learning difficulties, and solutions that can be used to improve the quality of education. This research uses a qualitative approach by applying library research. Information is obtained through the analysis of three primary journals and several additional references that discuss learning challenges in IS subjects. Data collection is conducted through documentation, while data analysis uses content analysis. The research findings indicate that the main challenges in IS learning consist of low student interest in learning, monotonous teaching methods, a lack of visual media, limited learning resources, and students difficulties in understanding historical material that is chronological and conceptual in nature. In addition, students often feel bored, lack concentration, and easily forget material that has been learned. Steps that can be taken to overcome these problems include implementing active and varied learning methods, utilizing digital and visual media, connecting historical material with everyday life, and improving teachers' abilities in learning innovation.